Assessment of the Sustainability of Community-owned (non-financial) Business Associations - Kocziszky, György; Veresné Somosi, Mariann (Public Finance Quarterly, 2020)
The community-owned non-financial business associations are playing an important role in the economy of Hungary and in shaping the social and political mood of our country. The main reason for this is that companies (e.g. health, transport, energy supply, district heating, water utilities, etc.) are in state or local governmental property, which have strategic importance, and can fundamentally influence the public mood by the quality, reliability and pricing of their services. Therefore, the efficiency of their operation, their financial position, their employability, their productivity, and the short and long term sustainability of their capital ratio have an impact on the social well-being. This social sensibility imposes an increased responsibility on the one hand on the maintainers of community-owned companies, and on the other hand on the management of organizations. Therefore, it does matter how and under what conditions these organizations can be maintained. In their study, the authors (after justifying the choice of topic) seek the answer for the following questions: How can be defined the sustainable community company? What are the indicators and how can be measured the sustainability of community companies? What conclusions can be drawn from the indicators, sub-indices and of the index change?